2020
DOI: 10.1177/0391560320974891
|View full text |Cite
|
Sign up to set email alerts
|

Relative position of bladder neck to pubic symphysis on cystogram is a strong and reproducible predictor of early urinary continence recovery following radical prostatectomy

Abstract: Objectives: To assess whether bladder neck angle and position on cystogram predict early urinary continence in patients scheduled for early catheter removal after radical prostatectomy (RP). Methods: A total of 103 patients undergoing open or robot-assisted RP by one expert surgeon between January and December 2019 were retrospectively analyzed. A cystogram was performed on postoperative day 3 or 4 to evaluate anastomotic leakage, and, if none or minimal, the catheter was removed. Urinary continence was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Following our pilot study, other studies have confirmed the predictive value of the three specific cystography features for PPI mentioned in our study: more of a downward bladder neck level [ 16 , 19 , 20 , 22 , 24 ], a sharp bladder neck angle [ 18 ], and anastomosis leakage [ 21 ] are associated with a delayed and lower probability of recovery from PPI.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Following our pilot study, other studies have confirmed the predictive value of the three specific cystography features for PPI mentioned in our study: more of a downward bladder neck level [ 16 , 19 , 20 , 22 , 24 ], a sharp bladder neck angle [ 18 ], and anastomosis leakage [ 21 ] are associated with a delayed and lower probability of recovery from PPI.…”
Section: Discussionsupporting
confidence: 83%
“…Specific features included a downward bladder neck, the bladder neck angle, and anastomosis leakage [ 15 ]. The predictive value of these specific features in cystography for PPI is now well established [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%